圆柱分度凸轮单侧面加工原理及刀位控制方法研究 - 尹明富; 赵镇宏; 于楷 (Jixie chuandong)
A new cutting tool control method of one-side processing for cylindrical indexing cam is proposed. Without increasing the coordinated axes of numerical control machine, one-side processing for cylindrical indexing cam is realized, and a mathematical model of cutting tolls control method is established. This technology overcomes the shortage of the equivalent-radius enveloping method, improves the machining accuracy and the quality of contour surface, increases the life span of the tools, and also economically realizes the grinding of the cam.